Trauma-Informed Care: A Missing Link in Addressing Burnout - Elisseou S (Dove Medical Press, 2023)
Sadie Elisseou1,2 1Department of Medicine, Harvard Medical School, Boston, MA, USA; 2Department of Medicine, Boston University School of Medicine, Boston, MA, USACorrespondence: Sadie Elisseou, Harvard Medical School, 22 Shattuck St., Boston, MA, 02115, USA, Tel +1 617-752-2689, Fax +1 774-826-3157, Email Sadie.Elisseou@va.govAbstract: The Covid-19 pandemic and national movements for health equity have highlighted the impact of trauma on public health as well as on health worker well-being. As burnout rates across healthcare climb, we seek creative and effective solutions. Current anti-burnout strategies focus on much needed systems solutions for employee success; however, they often lack a trauma-informed approach. Trauma is highly prevalent in society at large, and health workers are further exposed to trauma in the course of their professional studies and duties. Common symptoms of burnout may actually be manifestations of traumatic stress. Trauma-informed care (TIC) is a strategic framework and growing social movement for providing quality care to survivors of individual, interpersonal, collective, and structural trauma. Importantly, TIC has practical applications to address our healthcare burnout epidemic. In this perspective piece, an expert describes a trauma-informed lens through which to view burnout solutions using SAMHSA's 4 Rs of a trauma-informed approach: 1) Realize the widespread impact of trauma, 2) Recognize the signs and symptoms in patients and staff, 3) Respond by integrating knowledge about trauma into practice, and actively 4) Resist re-traumatization. Moving forward, key stakeholders must collaborate to build and refurbish efficient systems alongside a trauma-informed organizational model. TIC can transform the healthcare experience for patients and employees alike by fostering community, empowerment, and healing.Keywords: burnout, trauma, trauma-informed, mental health, healthcare